2000
DOI: 10.4269/ajtmh.2000.62.681
|View full text |Cite
|
Sign up to set email alerts
|

Phase II safety and immunogenicity study of live chikungunya virus vaccine TSI-GSD-218.

Abstract: Abstract. We conducted a phase II, randomized, double-blind, placebo-controlled, safety and immunogenicity study of a serially passaged, plaque-purified live chikungunya (CHIK) vaccine in 73 healthy adult volunteers. Fiftynine volunteers were immunized one time subcutaneously with the CHIK vaccine and 14 were immunized with placebo (tissue culture fluid). Vaccinees were clinically evaluated intensively for one month, and had repeated blood draws for serological assays (50% plaque-reduction neutralization test)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
229
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(241 citation statements)
references
References 16 publications
4
229
0
5
Order By: Relevance
“…No vaccine is currently available for use; however, phase II safety and immunogenicity study of live CHIK vaccine TSI-GSD-218 had been undertaken in Maryland. [38] Although there were indications that other alpha virus vaccines may interfere with the immune response of live CHIK vaccine, this was found to be highly immunogenic as neutralizing antibodies were detected in 85% of the volunteers after 12 months. Long-term follow-up studies would be needed to determine the durability of immune response.…”
Section: Points To Ponder On the Ongoing Outbreak And The Challenges mentioning
confidence: 98%
See 1 more Smart Citation
“…No vaccine is currently available for use; however, phase II safety and immunogenicity study of live CHIK vaccine TSI-GSD-218 had been undertaken in Maryland. [38] Although there were indications that other alpha virus vaccines may interfere with the immune response of live CHIK vaccine, this was found to be highly immunogenic as neutralizing antibodies were detected in 85% of the volunteers after 12 months. Long-term follow-up studies would be needed to determine the durability of immune response.…”
Section: Points To Ponder On the Ongoing Outbreak And The Challenges mentioning
confidence: 98%
“…The vaccine was found to be safe; it produced well-tolerated side-effects such as transient arthralgia in 8% of individuals. [38] Further results are awaited as this appears to be a promising vaccine for use in alpha virus naïve individuals. Until then, prevention and control activities are to be targeted at vector source reduction.…”
Section: Points To Ponder On the Ongoing Outbreak And The Challenges mentioning
confidence: 99%
“…The latter may be explain the residual reactogenicity of alphavirus vaccines that rely on point mutations that accumulate during cell passages, including attenuated strains of Chikungunya virus [23] and VEEV [24]; 2) the success of the chimeric flavivirus vaccines also argues for this approach [25]; 3) live-attenuated vaccines have advantages over other approaches (e.g. subunit and inactivated vaccines) of rapid and long-lasting immunity, including both cellular and humoral.…”
Section: Introductionmentioning
confidence: 99%
“…A liveattenuated vaccine TSI-GSD-218 has also been advanced into phase II clinical trials. In a double-blind, randomized, placebo-controlled study of vaccine in 73 healthy adult volunteers, this vaccine was demonstrated to be safe and highly immunogenic, but associated with transient arthralgia in five vaccinees (Edelman et al, 2000).…”
Section: Vaccine Research and Developmentmentioning
confidence: 99%